2018
DOI: 10.1091/mbc.e18-02-0142
|View full text |Cite
|
Sign up to set email alerts
|

The I1 dynein-associated tether and tether head complex is a conserved regulator of ciliary motility

Abstract: We characterized the composition and three-dimensional structure of a conserved, dynein-associated tether/tether-head complex and its interactions with other ciliary structures. The complex is a conserved regulator of I1 dynein and a “missing link” within the signaling pathway that is critical for control of ciliary motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 55 publications
10
80
0
Order By: Relevance
“…We rescued the pf16 mutant with wild-type PF16 C-terminally tagged with BCCP. Axonemes of the rescued strain were isolated, and the biotinylated tag was enhanced with streptavidin-nanogold, which is visible as additional cryo-EM density in comparison to the wild-type structure Fu et al, 2018). Tomograms of the pf16;PF16::BCCP rescue showed only "9+2" axonemes and all CA projections were restored to the wild-type architecture with and without (control) addition of streptavidin-gold ( We were unable to rescue the pf16 mutant with N-terminally tagged PF16, possibly because the PF16 N-terminus is required for protein-protein interactions and assembly of the C1a-e-c supercomplex, or the N-terminal BCCP tag (9 kDa) disrupts PF16 folding or its transport into the axoneme.…”
Section: Pf16 a C1a Projection Subunit Is Required For C1a-e-c Compmentioning
confidence: 99%
See 3 more Smart Citations
“…We rescued the pf16 mutant with wild-type PF16 C-terminally tagged with BCCP. Axonemes of the rescued strain were isolated, and the biotinylated tag was enhanced with streptavidin-nanogold, which is visible as additional cryo-EM density in comparison to the wild-type structure Fu et al, 2018). Tomograms of the pf16;PF16::BCCP rescue showed only "9+2" axonemes and all CA projections were restored to the wild-type architecture with and without (control) addition of streptavidin-gold ( We were unable to rescue the pf16 mutant with N-terminally tagged PF16, possibly because the PF16 N-terminus is required for protein-protein interactions and assembly of the C1a-e-c supercomplex, or the N-terminal BCCP tag (9 kDa) disrupts PF16 folding or its transport into the axoneme.…”
Section: Pf16 a C1a Projection Subunit Is Required For C1a-e-c Compmentioning
confidence: 99%
“…The pf28 and pf16 (Zhao et al, 2019), which served as the control. As previously described (Fu et al, 2018),…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Tetrahymena, CFAP57 is placed adjacent to the FAP43/44 complex based on proximity mapping (6). Comparative proteomics analysis of I1/f and FAP43/44 mutants showed that the I1 dynein and the T/TH complex assemble independently of each other (56). The fap57 mutants assemble the Il/f twoheaded dynein complex properly as well (Table 3).…”
Section: Discussionmentioning
confidence: 99%